Resistome, mobilome, and virulome explored in clinical isolates derived from acne patients in Egypt: unveiling unique traits of an emerging coagulase-negative Staphylococcus pathogen - Amer, Mai A.; Darwish, Manal M.; Soliman, Noha S.; Amin, Heba M. (Frontiers in Cellular and Infection Microbiology, 2024)
Coagulase-negative staphylococci (CoNS), is a group of Gram-positive staphylococcal species that naturally inhabit healthy human skin and mucosa. The clinical impact of CoNS-associated infections is recently regarded challenging in their diagnosis, and therapeutic options. The CoNS-associated infections are primarily caused by the bacteria's resistance to antibiotics and biofilm formation. Since antibiotics are still the most commonly used treatment, this problem will likely persist in the future. The present study aims to investigate the resistance and virulence of CoNS recovered from various acne lesions, along with exploring their genetic basis. Skin swab samples were gathered from participants exhibiting acne and healthy skin. All samples underwent conventional culture for isolation of CoNS, MALDI-TOF confirmation, antibiotic susceptibility, and biofilm formation testing. A total of 85 CoNS isolates were recovered from samples; preliminary identified as Staphylococcus epidermidis. Isolates from the acne group (n=60) recorded the highest rates of resistance to penicillin (73%), cefoxitin (63%), clindamycin (53.3%), and erythromycin (48%), followed by levofloxacin (36.7%) and gentamycin (31.7%), while the least rates of resistance were observed for tetracycline (28.3%), doxycycline (11.7%) and minocycline (8.3%). CoNS isolated from mild, moderate acne and healthy isolates did not show strong biofilm formation, while the isolates from the severe cases of the acne group showed strong biofilm formation (76.6%). Four extensively drug-resistant and strong biofilm-forming staphylococcal isolates recovered from severe acne patients were selected for whole-genome sequencing (WGS), and their genomes were investigated using bioinformatics tools. Three of the sequenced genomes were identified as S. epidermidis, however, isolate 29AM was identified as Staphylococcus warneri, which is a newly emerging pathogen not commonly associated with acne and was not detected by MALDI-TOF. Only the S. warneri isolate 29AM contained immune evasion genes (capB, capC, acpXL, and manA), anti-phagocytosis gene (cdsA), and other unique features. As a result of their potential pathogenicity and antibiotic resistance, CoNS has to be monitored as an emerging pathogen correlated with acne infections. To the best of our knowledge, this is the first report to isolate, identify, and correlate S. warneri with severe acne infections among Egyptian patients revealed by WGS and bioinformatics analysis.